Influence of bunch maturation and chemical precursors on acrylamide formation in starchy banana chips - Udomkun, Patchimaporn; Swennen, Rony L.; Masso, C.; Innawong, B.; Fotso Kuate, A.; Alakonya, A.; Vanlauwe, Bernard (Wiley, 2021)
The present study investigated the effect of ripening stages and chemical precursors on acrylamide formation in deep-fried chips of five plantains and one cooking banana. The highest level of acrylamide was found in the cooking banana, followed by False Horn plantain and French plantain, respectively. French plantain hybrids exhibited a significantly lower (P < 0.05) level of acrylamide when compared to French plantain. The ripening stage demonstrated a positive Pearson correlation (P < 0.05, r = 0.57) with acrylamide formation. As ripening progressed, the levels of glucose and fructose significantly increased (P < 0.05) and showed a positive correlation with acrylamide formation (r = 0.85 and 0.96, respectively). The level of the amino acid asparagine during ripening was not correlated with acrylamide formation. In contrast, the level of histidine, arginine, iso-leucine and cystine during ripening was positively correlated (P < 0.05, r > 0.60) with acrylamide formation in fried chips. The higher level of TP was significantly related (P < 0.05) to the lower level of acrylamide (r = −0.62). The reduced levels of carotenoid isomers, except lutein, during fruit ripening were positively correlated (P < 0.05) with acrylamide formation, especially trans-BC (r = 0.72) and 9-cis-BC(r = 0.64).